EP1223 Fertility-sparing surgery in patients with borderline ovarian tumors and reproductive outcomes. (1st November 2019) - Helmut, P; Harter, P; Ataseven, B; Heitz, F; Prader, S; Schneider, S; Heikaus, S; Traut, A; du Bois, A
Abstract : Introduction/Background: Borderline ovarian tumours (BOTs) are recognized as a unique entity of ovarian tumours that do not exert infiltrative destructive growth or stromal invasion. BOTs occur often in young patients and fertility sparing surgery (FSS) is an important issue. With this study we aimed to evaluate relapses and fertility of patients after FSS. Methodology: Patients with BOT were included from our prospective registry database between 2000–2018. An external histopathological review was conducted in all cases. FSS was performed after individual discussion, a complete staging was defined according to FIGO, without lymphadenectomy and with a waiver for preservation of uterus and one ovary in case of FSS. Prognostic factors for Recurrence-Rates (RR) and data on fertility were studied. Results: Among 352 Patients 80.2% had FIGO-Stage I disease and 63.9% had a serous BOT. 95 patients underwent FSS. After a median follow-up of 63 months 19 patients (5.4%) relapsed; in 5 cases a malignant transformation was reported (1.4%). After FSS 13 patients relapsed, all as BOT. The all-over recurrence-rate (RR) was 1.4% in FIGO-Stage I and 25.5% in FIGO III-IV (HR20; 95%-CI 6.6–62; p≤ 0.001). The corresponding RRs for Radical Surgery (RS) in stage I were 0.5%, in stage II-IV 9.8% and for FSS in stage I 3.9% and 55.6% in stage II-IV. In multivariate analysis stage II-IV (HR=22; 95%-CI: 7.2–77; p≤ 0.001) and FSS (HR=11; 95%-CI: 2.9–44; p=0.003) remained significant risk factors for recurrent disease. 36 patients (37.9%) had pregnancy desire. The cumulative incidence of first pregnancy was 77.7%. 28 patients experienced at least one term pregnancy, in total 36 Life-births were reported. Conclusion: FSS in stage I is a safe procedure. In other stages FSS has to be discussed individually. An external second opinion regarding pathology is mandatory, this might explain partially our low rate of invasive relapses. Life-birth-rates after FSS are high. Disclosure: H. Plett: nothing to disclose. P.Harter: Honoraria: Astra Zeneca, Roche, Sotio, Tesaro, Stryker, ASCO, Zai Lab, MSD; Advisory Board: Astra Zeneca, Roche, Tesaro, Lilly, Clovis, Immunogen, MSD/Merck; Research funding (Inst): Astra Zeneca, Roche, GSK, Boehringer Ingelheim, Medac, DFG, European Union, DKH, Tesaro, Genmab F. Heitz: Honoraria: AstraZeneca, Roche, Tesaro, Clovis; Advisory Board: Astra Zeneca, Roche, Tesaro, Clovis A. du Bois: personal fees from Roche, personal fees from Astra Zeneca, personal fees from Tesaro, personal fees from Clovis, personal fees from Pfizer, personal fees from Genmab, personal fees from Pharmar, personal fees from Biocad, outside the submitted work; B. Ataseven: Roche Advisory board, lecture, travel/accommodation expenses Tesaro Advisory board, travel/accommodation expenses Amgen Advisory board Celgene lecture PharmaMar travel/accommodation expenses Clovis lecture Astra Zeneca lecture S. Schneider: Roche: lecture Tesaro: Advisory board, lecture, travel/accommodation expenses Clovis: lecture Astra: Zeneca lecture A. Traut, S. Prader, S. Heikaus: nothing to disclose.